Language and Identity: A Modern Exploration in Globalized Societies - Shakhnoza Sharofova (Genius Publishing Group, 2024)
This article explores the intricate relationship between language and identity in the context of today's globalized societies. As the world becomes increasingly interconnected, linguistic diversity emerges as a key marker of cultural richness, shaping individual and communal identities. The intersection of language and culture highlights both the inclusive potential and challenges associated with maintaining linguistic heritage. Migration introduces the dynamic element of hybrid identities, while technological advances reshape language evolution and expression. The article also delves into the role of language policy in fostering global citizenship. Ultimately, it contends that a nuanced understanding of the interplay between language and identity is crucial for cultivating inclusive and harmonious societies in an ever-evolving global landscape
Keywords: Language; LanguageGlobalized Societies